A study of internet addiction and its effects on mental health: A study based on Iranian University Students - Javad Yoosefi Lebni; Razie Toghroli; Jaffar Abbas; Nazila NeJhaddadgar; Mohammad Reza Salahshoor; Morteza Mansourian; Hadi Darvishi Gilan; Neda Kianipour; Fakhreddin Chaboksavar; Seyyed Amar Azizi; Arash Ziapour (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: The Internet has drastically affected human behavior, and it has positive and negative effects; however, its excessive usage exposes users to internet addiction. The diagnosis of students' mental dysfunction is vital to monitor their academic progress and success by preventing this technology through proper handling of the usage addiction. MATERIALS AND METHODS: This descriptive-analytical study selected 447 students (232 females and 215 males) of the first and second semesters enrolled at Kermanshah University of Medical Sciences, Iran, in 2018 by using Cochrane's sample size formula and stratified random sampling. The study applied Young's Internet Addiction Test and Goldberg General Health Questionnaire 28 for data collection. The study screened the data received and analyzed valid data set through the t-test and Pearson's correlation coefficient by incorporating SPSS Statistics software version 23.0. RESULTS: The results of the current study specified that the total mean score of the students for internet addiction and mental health was 3.81 ± 0.88 and 2.56 ± 0.33, correspondingly. The results revealed that internet addiction positively correlated with depression and mental health, which indicated a negative relationship (P > 0.001). The multiple regression analysis results showed students' five significant vulnerability predictors toward internet addiction, such as the critical reason for using the Internet, faculty, depression, the central place for using the Internet, and somatic symptoms. CONCLUSIONS: The study findings specified that students' excessive internet usage leads to anxiety, depression, and adverse mental health, which affect their academic performance. Monitoring and controlling students' internet addiction through informative sessions on how to use the Internet adequately is useful.